TURN TAKING IN INDONESIA TRADITIONAL MARKE - Friska Simanjuntak; Meisuri Meisuri (Universitas Negeri Medan, 2019)
This current study aimed to examine the turn-taking strategies that are used by sellers and buyers at Horas traditional market, Pematangsiantar. This study wants to show the process of turn-taking between sellers and buyers when taking their turn. Especially on take the turn when sellers and buyers do bargaining process. It means that which can look at how the sellers and buyers manage and take to the first current or exchange of talking turn in interaction. The data will analyze using Sack Schegloff, and Jefferson (1974) theory which is divided into three kinds, Current Speaker Select the Next Speaker, Self Select, Current Speaker Continuous. The data is collected by doing a recording video about the interaction between sellers and buyers, Pematangsiantar. The researcher found 40 data to support this study. Based on the result, the dominant strategy used by sellers and buyers is Current Speaker Select the Next Speake (50%), the next dominant is Self Select (32,5%), the last strategy is Current Speaker Continuous (17,5). The reason to use the dominant types is that the situation that often occurs is one buyer and one seller, so it can be ascertained that when the buyer becomes the current speaker, the next speaker is the seller, and vice versa. This study also showed that the most buyer does interact with seller is female buyers. It makes that the process of bargaining here needs a long time, different for male buyers, they only make on the bargain